Will climate change shift carbon allocation and stem hydraulics? Insights on a systemic view of carbon- and water-related wood traits in an anysohydric tropical tree species (Hymenaea courbaril, Leguminosae) - Bernardo Pretti Becacici Macieira (Elsevier, 2021)
Tropical forests uptake more atmospheric CO2 and transpire more water than any other forest in the world and are critical components of the global carbon and hydrological cycles. Both cycles depend to a great extent on the carbon and water balance of individual trees. Such adjustments are usually evaluated through well-established and newly-emerging traits but integrating them for a systemic understanding of trees' responses to climate change can be challenging. We propose using complex correlation networks to integrate and understand how trees coordinate water- and carbon-related traits under changing climate conditions. We built a correlation network based on 20 traits measured in the wood of Hymenaea courbaril (Leguminosae) trees, a species known for its extreme anisohydric water-use strategy, sampled along a climate gradient in Southeastern Brazil. Intercellular to ambient CO2 concentrations ratio (ci/ca, estimated from tree-ring δ13C) is a central network trait for being coordinated with several hydraulic and carbon allocation traits. Trees of H. courbaril coordinate these traits along the climate gradient, favoring high ci/ca under warm and dry conditions. A high ci/ca is only possible through a consistent water supply provided by wider vessels together with the investment on soluble sugars, at the detriment of starch, likely for hydraulic maintenance. Trees also favor heat resistance by investing in cell-wall xylose, another central network trait, from xyloglucans and xylans, at the expense of mannose from glucomannans. Such trade-offs within, and between, structural and non-structural carbon allocation reflect well-known metabolic pathways in plants. In summary, this systemic approach confirms previously reported patterns on leaf physiology, stem hydraulics and carbon adjustments while bringing to light the previously unreported role of cell-wall composition and its fine adjustments to cope with climate change.